PENERAPAN DWANGSOM DALAM PUTUSAN HAKIM SEBAGAI EFEKTIFITAS PERTANGGUNGJAWABAN KORPORASI TERHADAP PEMULIHAN LINGKUNGAN - Andi Hakim Lubis; Fahrizal S. Siagian; Windy Sri Wahyuni; Rismanto J. Purba (Jurnal Yuridis, 2025)
Corporate activities often cause widespread ecological and social damage to the environment, while existing legal instruments have not been effective in ensuring the implementation of environmental restoration obligations. Therefore, the application of dwangsom (coercive fines) through court rulings can be a progressive legal breakthrough. This study analyses the role of dwangsom as a legal instrument in encouraging corporate compliance with environmental restoration obligations and assesses its compatibility with the principles of justice, legal certainty, and benefit. The method used is a normative juridical approach through a review of legislation, jurisprudence, and legal literature. The results of the study show that dwangsom plays a strategic role as a means of coercion to increase corporate compliance with court rulings. However, its effectiveness still faces normative and practical obstacles, such as regulatory limitations, differences in judicial interpretation, and weak enforcement mechanisms. Therefore, regulatory strengthening and consistency in judicial practice are needed.